Technopolis in Baikalsk: eco-innovation cluster - Druzhinina, Inna; Zhmykhova, Anastasia (project baikal, 2019)
The article describes the potential threats of the changes in the sustainability of the ecological system of lake Baikal which have resulted from the industrial activities of the Baikal Pulp and Paper Mill. In this urban planning project, it is proposed to create the technopolis on this basis. It is an eco-innovation cluster that is focused on the commercialization of innovative ecological developments in the Baikal Region. It aims to improve the efficiency of the scientific potential of Eastern Siberia.
Keywords: environmental threat; a company town Baikalsk; Baikal Pulp and Paper Mill; technopolis; innovative cluster; reorganization of industrial areas